2012
DOI: 10.3109/09513590.2011.650745
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from ovarian hyperstimulation following the sole administration of gonadotrophin-releasing hormone agonist in the context ofin vitrofertilization: report of two cases and review of the literature

Abstract: The ovarian hyperstimulation after the sole administration of GnRHa is a rare condition. Oocyte retrieval may be a reasonable treatment under these circumstances instead of cycle cancellation. As far as it is known, this is the third case reported of a live birth following the sole administration of GnRHa in the context of IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In several case reports, women scheduled for COH-IVF presented with multiple follicles development and high E2 levels within or after 2 weeks of GnRH agonist daily administration during the mid or late luteal phase [42][43][44]. It was reported that the retrieval of mature oocytes in luteal phase and embryo were obtained [42][43][44], as well as two pregnancies with the delivery of healthy infants [43,44].…”
Section: The Follicular Recruitment In Human Luteal Phasementioning
confidence: 99%
See 1 more Smart Citation
“…In several case reports, women scheduled for COH-IVF presented with multiple follicles development and high E2 levels within or after 2 weeks of GnRH agonist daily administration during the mid or late luteal phase [42][43][44]. It was reported that the retrieval of mature oocytes in luteal phase and embryo were obtained [42][43][44], as well as two pregnancies with the delivery of healthy infants [43,44].…”
Section: The Follicular Recruitment In Human Luteal Phasementioning
confidence: 99%
“…It was reported that the retrieval of mature oocytes in luteal phase and embryo were obtained [42][43][44], as well as two pregnancies with the delivery of healthy infants [43,44]. The possible explanation could be that recruitable follicles were present in luteal phase despite the presence of a functioning corpus luteum and increased levels of P. These follicles were able to respond to the "flare-up" of FSH produced by the GnRH-a and progress into mature follicles within 14 days [43].…”
Section: The Follicular Recruitment In Human Luteal Phasementioning
confidence: 99%